Molecular characterization and role in virus infection of Beclin-1 in large yellow croaker (Larimichthys crocea). Issue 116 (September 2021) - Wei, Zuyun; Li, Xiaofeng; Li, Wanru; Fu, Qiuling; Mu, Yinnan; Chen, Xinhua
Abstract: Beclin-1, the ortholog of yeast autophagy-related gene 6 (Atg6), has a central role in autophagy, which has been linked to diverse biological processes including immunity, development, tumor suppression, and lifespan extension. However, understanding of function of fish Beclin-1 is limited now. In this study, the complete Beclin-1 cDNA of large yellow croaker Larimichthys crocea ( Lc Beclin-1) was cloned, whose open reading frame (ORF) is 1344 bp long and encodes a protein of 447 amino acids (aa). The deduced Lc Beclin-1 possesses a typical Bcl-2 homology domain 3(BH3) and an APG6 domain that contains a central coiled-coil domain (CCD, residues 174 to 231) and a C -terminal evolutionarily conserved domain (ECD, residues 241 to 334). Lc Beclin-1 shared a high amino acid identity of 81.66–98.66% with reported Beclin-1 molecules from other vertebrate species. Lc Beclin-1 gene was constitutively expressed in all tissues tested, with the highest levels in heart. Lc Beclin-1 transcripts were also detected in primary head kidney granulocytes (PKGs), primary head kidney macrophages (PKMs), primary head kidney leukocytes (PKLs), and large yellow croaker head kidney cell line (LYCK), and were significantly upregulated by poly (I:C) in PKMs and LYCK cells. Subcellular localization showed that Lc Beclin-1 was evenly distributed in the cytoplasm and nucleus of LYCK cells. Overexpression of Lc Beclin-1 significantly increased the replication of SVCV, as evidenced by increased severity of the cytopathic effects, enhanced viral titre, and upregulated transcriptional levels of viral genes. Further studies showed that Lc Beclin-1 induced the occurrence of autophagy in LYCK cells. Additionally, Lc Beclin-1 also decreased the expression levels of large yellow croaker interferons (IFNs; IFNc, IFNd, and IFNh), interferon regulatory factor 3 (IRF3) and IRF7, IFN-stimulated genes (ISGs; Mx, PKR, and Viperin) in LYCK cells. All these data suggest that Lc Beclin-1 promoted the viral replication possibly by inducing autophagy or negatively modulating IFN response, which will help us to further understand the function of fish Beclin-1. Highlights: Lc Beclin-1 was constitutively expressed in tissues and immune cells, and upregulated in LYCK and PKMs cells by poly (I:C). Lc Beclin-1 was evenly distributed in the cytoplasm and nucleus of LYCK cells. Overexpression of Lc Beclin-1 promoted SVCV replication in EPC cells. Lc Beclin-1 negatively regulated the IFN system genes responses to achieve its proviral functions.